The Release of Total Metal Ion and Genotoxicity of Stainless Steel Brackets: Experimental Study Using Micronucleus Assay - Irene Karlina; Rahmi Amtha; Boedi Oetomo Roeslan; Yuniar Zen (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Stainless steel brackets are composed of various metal that may corrode in oral cavity. Corrosion is caused by the release of metal ions such as chromium, nickel, and iron. The release of metal ions can cause adverse effects such as toxicity, allergic, and mutagenicity. To evaluate the biocompatibility of stainless steel brackets, micronucleus assay as one of genotoxicity assay is used in this study. To determine the differences and the correlation of metal ions release and genotoxic activity among three brand stainless steel brackets.METHODS: Three brands of brackets were immersed in artificial saliva for 672 hours and the release of ion chromium, nikel and iron were examined. The cytokynesis block micronucleus assay (CBMN) using lymphocytes was performed as well.RESULTS: The highest metal releasing were nickel, cromium, iron, respectively (30.5, 27.2, 23.4 ppb). There was a significant differences between total nickel and iron ion release among three brand brackets (p=0.04, p=0.02). Genotoxicity of metal ion released was correlated with durration of immersion brackets (p=0.01). Genotoxicity was significant correlated with the release of chromium (p=0.03) and nickel (p=0.01).CONCLUSION: Genotoxicity of stainless steel brackets was influenced by duration of immersion but not influenced by brand brackets. KEYWORDS: genotoxicity, stainless steel brackets, metal ion